A Revista Nova Escola e a construção de identidades do professor - Beloti, Adriana (2011)
This research assumes that, currently, the means of communication and, consequently, production and circulation of effects of meanings in society are modified over the years, being the media a great example of where those discursive practices happen. Therefore, we believe it is impossible to reflect on the identity processes of the individuals without considering the media as one of the main places of enunciation where representations and social identities are staged and constructed. Thus, we start from the premise that the subject teacher undergoes excessive influences and changes due to social, historical and cultural factors. It must be added to this, the relations of knowledge and power, which influence the teaching practice directly, imprinting behaviors this way, therefore constructing identities for this individual. In order to analyze this process of identity production, we take as corpus of study the Nova Escola magazine, an educational publication that has already been consolidated in Brazilian publishing market, as it has been running since 1986 achieving significant numbers. The utterances materialized in the data we assembled show how this magazine contributes to the construction of teacher's identities, establishing relationships of knowledge and power regarding how the teaching practices should be, building from its utterances, forms of subjectivity of the subject teacher. Our study is based on the perspective of Cultural Studies, in particular the work of Stuart Hall (2005) and Bauman (2001, 2005), regarding the "crisis of identity" as well as characteristics of the present phase, considered as the era of globalization, and also as liquid, and the work developed by the philosopher Michel Foucault (2007a, 2007b, 2009a, 2009b), prominently, the notions of speech, utterance and subjective processes. Through this theoretical, methodological and analytical support, which has as its main basis the archeogenealogy made possible by Foucault's studies, we tried, through the description and interpretation of utterances of this media vehicle, understand the construction processes of the subject teacher identity in discourses present in Nova Escola magazine, once we take the production of identities as a fact of discourse.